(untitled) (Indian Journal of Animal Production and Management, 2026)
Background: Castration under general anesthesia is clinically meaningful, but there are potential physiological risks related to respiratory function and hematological stability. Only with a better understanding of these effects can anesthetic protocols be refined for optimal surgical outcomes. Aims: This study explores the physiological impact of general anesthesia on peripheral oxygen saturation (SpO₂) and hematological parameters in male dogs undergoing elective castration at three time points: pre- (baseline), during (mid-surgery), and post (recovery) anesthesia. Results: Oxygen saturation declined significantly during anesthesia (86.16 ± 4.67 %) compared with baseline (99.00 ± 0.00 %) and partially recovered post-anesthesia (95.83 ± 1.70 %) (P ≤ 0.01). Hematological analysis showed postoperative leukocytosis (WBC: 21.84 ± 5.94 × 10³/μL) and significant reductions in red blood cell count (8.17 ± 0.52 × 10⁶/μL), hemoglobin (9.45 ± 0.61 g/dL), and hematocrit (31.55 ± 3.36 %) compared with baseline (P ≤ 0.05–0.01). Red cell distribution width (RDW) and platelet distribution width (PDW) increased, whereas platelet count decreased, likely reflecting stress and hemodilution responses to anesthesia and surgery. Conclusion: General anesthesia during canine castration induces transient hypoxemia and distinct hematological alterations. Therefore, continuous perioperative respiratory monitoring and tailored anesthetic management are recommended to enhance recovery and minimize complications. These findings may assist veterinarians in refining anesthetic monitoring protocols for safer routine castration procedures. Further research with larger populations is needed to validate these observations and assess long-term physiological outcomes.